Utilizing Waste from the Natural Resources of Harapan Island to Become Kitchen/Pantry Decoration Elements in Residential Homes - Ulinata, Ulinata; Miracella, Jessica; Napitupulu, Yolanda (PT FORMOSA CENDEKIA GLOBAL, 2024)
Lecturers and students of the Architecture Study Program at the Christian University of Indonesia together in partnership with Antheia and Fempire once again held a Community Service on Harapan Island by raising the title